Dollarization and Economic Performance: What Do We Really Know? - Sebastian Edwards; I. Igal Magendzo (Oesterreichische Nationalbank (OeNB), 2002)
In this paper we analyze the macroeconomic record of dollarized economies. In particular, we investigate whether, as its supporters' claim, dollarization is associated with lower inflation and faster growth. We analyze this issue by using a matching estimator technique developed in the training evaluation literature. Our findings suggest that inflation has been significantly lower in dollarized nations than in non-dollarized ones. We also find that dollarized nations have had a lower rate of economic growth than non-dollarized ones. Finally, we find that macroeconomic volatility is not significantly different across dollarized and non-dollarized economies. We conjecture that the lower rate of economic growth in dollarized countries is due, at least in part, to these countries' difficulties in accommodating external disturbances, such as major term of trade and capital flows shocks.
Keywords: 330